82.9k views
3 votes
PLEASE HELP URGENT!!! Cannot figure this out, due tonight.

PLEASE HELP URGENT!!! Cannot figure this out, due tonight.-example-1
User Runr
by
4.9k points

1 Answer

4 votes

Answer:

  • f(x+h) = (2x² -x +2) +4xh -h +2h²
  • (f(x+h) -f(x))/h = 4x -1 +2h

Explanation:

Like a lot of algebraic manipulation associated with average rate of change, it is not difficult, but it can be tedious.

a)


f(x+h)=2(x+h)^2-(x+h) +2 = 2(x^2 +2xh +h^2)-x -h +2\\\\\boxed{f(x+h)=2x^2-x+2+4xh-h+2h^2}

__

b)

Then the difference quotient is ...


(f(x+h)-f(x))/(h)=((2x^2-x+2)+4xh-h+2h^2-(2x^2-x+2))/(h)\\\\=(4xh-h+2h^2)/(h)\\\\\boxed{(f(x+h)-f(x))/(h)=4x-1+2h}

User Vivek Sasidharan
by
4.7k points